Social media health literacy during a pandemic: Is everyone prepared for that? (Research, Society and Development, 2023)
The internet has been an important tool for health literacy, particularly during global impacts (e.g., the Sars-Cov-2 pandemic) however, one question remains: is everyone prepared for social media health literacy during a pandemic? This study aimed to describe the health literacy process provided via social media to artisanal fishermen during the Sars-Cov-2 pandemic. A descriptive study (experience report) on the development and implementation of educational actions for health promotion developed via social networks (Instagram, YouTube, and WhatsApp). Using digital platforms for health literacy is a viable, low-cost, and far-reaching alternative to disseminating information to vulnerable populations in times of pandemic (or in contexts where face-to-face is impossible). In conclusion, some artisanal fishermen do not have access to the internet, either because they live in rural areas, or because of conditions that make it impossible for them to acquire the equipment.